Advancements in BATTERY longevity of cardiac implantable electronic devices from real‐world data: BATTERY study - Maiko Kuroda; Michio Nagashima; Masataka Narita; Wataru Sasaki; Naomichi Tanaka; Kazuhisa Matsumoto; Tsukasa Naganuma; Hitoshi Mori; Yoshifumi Ikeda; Kengo Korai; Masato Fukunaga; Kenichi Hiroshima; et al. (Journal of Arrhythmia)
Abstract Background Technological development has improved the battery longevity of cardiac implantable electronic devices (CIEDs). However, there have been no reports on the extent of the improvement in battery longevity in the real world. Methods Patients who underwent CIED exchanges from February 2006 to June 2023 were included in this study. The actual battery longevity calculated from the implantation date to the battery replacement date and the predicted battery longevity based on manufacturer reports were investigated. All patients were divided into five groups according to their initial implantation dates. After excluding the first and last groups, the data among the middle three groups (P1, P2, P3) were compared. Results A total of 3119 patients (pacemakers [PMs], 2138; ICDs, 477; cardiac resynchronization therapy pacemakers [CRTPs], 121; cardiac resynchronization therapy defibrillators [CRTDs], 383) were enrolled in this study. The predicted device longevity improved over time for all devices, but in recent analyses, it has been overestimated compared to the actual device longevity for PMs, ICDs, and CRTPs. The actual device longevity of PMs, ICDs, and CRTDs exhibited an extension in the early two periods (P1 vs. P2), but no extension was observed in the most recent two periods (P2 vs. P3). CRTPs showed no improvement in any of the periods. Conclusion The battery longevity has improved by only about 1 year over the past nearly 15 years. Moreover, the discrepancy between the predicted and actual battery longevity suggests that a reevaluation of the methods for calculating the predicted battery longevity may be necessary.